Disc Hemorrhages Are Associated With the Presence and Progression of Glaucomatous Central Visual Field Defects. Issue 6 (June 2020) - Shukla, Aakriti G.; Sirinek, Portia E.; De Moraes, C. Gustavo; Blumberg, Dana M.; Cioffi, George A.; Skaat, Alon; Girkin, Christopher A.; Weinreb, Robert N.; Zangwill, Linda M.; Hood, Donald C.; Liebmann, Jeffrey M.
Abstract : Precis: In this prospective cohort study, disc hemorrhages were associated with more severe central damage on 24-2 and 10-2 visual fields (VFs), and faster progression globally on 24-2 VFs and centrally on 10-2 VFs. Purpose: To study the relationship between disc hemorrhage (DH) and the presence and progression of glaucomatous central VF damage. Methods: Cross-sectional and longitudinal analyses were performed on data from the African Descent and Glaucoma Evaluation Study (ADAGES) cohort. Two masked investigators reviewed disc photographs for the presence and location of DH. 24-2 central VF damage was based on the number of test locations within the central 10 degrees of the 24-2 field pattern deviation and their mean total deviation (MTD). 10-2 central VF damage was based on pattern deviation and MTD. Main outcome measures were the association between DH and presence of central VF damage and between DH and worsening of VF. Results: DH was detected in 21 of 335 eyes (6.2%). In the cross-sectional analysis, DH was significantly associated with more severe central damage on 24-2 [incidence rate ratio=1.47; 95% confidence interval (CI)=1.02-2.12; P =0.035] and 10-2 VFs (incidence rate ratio=1.81; 95% CI=1.26-2.60; P =0.001). In the longitudinal analysis, DH eyes progressed faster than non-DH eyes based on 24-2 global MTD rates (difference in slopes, β=−0.06; 95% CI=−0.11 to −0.01; P =0.009) and 10-2 MTD rates (β=−0.10; 95% CI=−0.14 to −0.06; P < 0.001), but not 24-2 central MTD rates (β=−0.02; 95% CI=−0.078 to 0.026; P =0.338). Conclusion: DH was associated with the presence and progression of central VF defects. DH identification should prompt intensive central VF monitoring and surveillance with 10-2 fields to detect progression.